A Comparative Study Of Mathematical Knowledge Of Students Studying Mathematics Through Vedic And Non-Vedic Methods - Pratibha Goplani; Dr. Pragya Jha (Journal for ReAttach Therapy and Developmental Diversities, 2023)
This paper presents a comparative analysis of the mathematical knowledge of students who study mathematics through Vedic and non-Vedic methods. The study aims to investigate whether there is a significant difference in mathematical proficiency between students taught using these two methodologies. Additionally, the study explores whether there is any disparity in mathematical knowledge concerning gender. Two hypotheses were formulated to guide the research: 1) There exists no significant difference in mathematical knowledge of students studying math through Vedic and traditional methods, and 2) There exists no significant difference in mathematical knowledge with respect to gender. The study employed quantitative research methods to collect and analyze data from a sample of students enrolled in mathematics courses taught using either Vedic or non-Vedic methods. The findings of the study provide valuable insights into the effectiveness of different teaching approaches in enhancing mathematical proficiency and addressing gender disparities in mathematical achievement